RESISTANCE TO COMPRESSION OF CONCRETE REINFORCED WITH POLYPROPYLENE FIBER - Obando-Guillermo, Humberto (2023)
The qualities of polypropylene fi bers accompanied by ideal materials such as concrete, have brought solid and resistant structures to all types of construction such as pavements, tunnels, roads, among others. The purpose of this paper is to examine the behavior of concrete reinforced with different types of fi ber, including polypropylene fi ber, in order to know its reaction to mechanical processes. A review of 50 articles was carried out between 2010 and 2021, including Scopus, Scielo, ScienceDirect and EBSCO databases, analyzing the effects of fi bers and their infl uence on the compressive strength of concrete. In order to know the improvements in the strength of concrete using polypropylene fi ber, the results obtained with different dosages of this fi ber are presented. We conclude that the use of polypropylene fi ber generates the following changes in the properties of the concrete: 1) Increase in its tensile capacity; 2) Decrease in the workability of the concrete and, 3) Increased ductility of the concrete. Keywords: Compressive strength – concrete – polypropylene fi bers